MULTIKULTURALISME DI INDONESIA: ANALISIS TOLERANSI DAN KONFLIK SOSIAL DALAM MASYARAKAT BERAGAM - Fadil Mas’ud; Alfret Benu; Wihelmina Ruli Loo; Kristina Desita Angul; Emirenciana Aek Bria; Suriyanti Ramadhani Soemowinoto; Angel Stefanie Nafa; Fadil Mas’ud (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study examines the dynamics of multiculturalism in Indonesia, focusing on the level of tolerance and conflict patterns in diverse societies. The aim is to understand how the principles of multiculturalism are implemented, the factors that build tolerance, and the causes of intergroup tensions. Using a descriptive qualitative approach through a literature review, document analysis, and brief interviews, this study found that the practice of tolerance is quite strong due to local cultural values, the role of community leaders, and government-supported policies. However, conflicts still arise due to political interests, economic inequality, stereotypes, and the spread of misinformation in digital media. These findings indicate that multiculturalism is not yet fully stable and needs to be strengthened through inclusive education, cross-cultural dialogue, and socially just policies. Multiculturalism remains a key foundation of unity that must be continuously maintained.